Determination of sparstolonin B by ultra‐high performance liquid chromatography coupled with triple quadrupole mass spectrometry: application to pharmacokinetic study of sparstolonin B in rat plasma. (2nd March 2015) - Zou, Nuo‐Shu; Liang, Qiao‐Li; Li, Ping; Liu, Jie; Liu, Xiao; Kang, An; Deng, Hai‐Shan
Abstract Sparstolonin B (SsnB), a spontaneous isocoumarin compound isolated from the tuber of Scirpus yagara Ohwi. (Cyperaceae), possesses potent anti‐inflammatory and antitumor activity. In the present study, a rapid and simple UHPLC/MS/MS method for determination of SsnB in rat plasma was developed and validated. Plasma samples were pretreated by liquid–liquid extraction with ethyl acetate containing rhein as an internal standard and separated on a C18 column at 35 °C, with a gradient mobile phase consisting of acetonitrile and water containing 0.2% (v/v) formic acid within 2.1 min. MS/MS detection was accomplished in multiple reaction monitoring mode with negative electrospray ionization. The precursor–product ion transitions were m/z 266.9 [M–H]− → m/z 211.0 for SsnB and m/z 283.2 [M–H]− → m/z 239.0 for IS. The intra‐ and inter‐day precision (RSD) was <8.98% and the accuracy (RE) ranged from −7.40 to 4.50%. The extraction recoveries ranged from 96.28 to 97.30%. The pharmacokinetic parameters were calculated using Win Nonlin53 software. The absolute bioavailability of SsnB was estimated to be 6.98%. The proposed method was successfully applied to a pharmacokinetic study of SsnB in rats after intravenous administration with a dose of 0.5 mg/kg and oral administration at a dose of 5 mg/kg. Copyright © 2015 John Wiley & Sons, Ltd.